2020
DOI: 10.21873/anticanres.14047
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-term Outcomes of Esophagectomy for Esophageal Cancer in Patients Older than 75 Years

Abstract: Background: The short-and long-term outcomes of esophagectomy for esophageal cancer were fully evaluated in patients older than 75 years of age. Patients and Methods: The present study selected patients who received esophagectomy for esophageal cancer. Patients were divided into non-elderly patients [age <75 years (nonelderly group)] and elderly patients [age ≥75 years (elderly group)]. The postoperative surgical morbidity, postoperative 30-days mortality, recurrence-free survival (RFS), and overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Among the 19 studies assessing anastomotic leakage for EP versus YP, none revealed a difference in the incidence of this complication ( Table 1 ) [ 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Anastomotic leakage rates presented considerable variability, reaching 25–37.5% for series with cervical anastomoses [ 31 , 35 , 43 ]. Schweigert et al reported a significantly increased postoperative mortality (OR = 8.24, p = 0.025) for EP compared to YP who present an anastomotic leakage [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 19 studies assessing anastomotic leakage for EP versus YP, none revealed a difference in the incidence of this complication ( Table 1 ) [ 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Anastomotic leakage rates presented considerable variability, reaching 25–37.5% for series with cervical anastomoses [ 31 , 35 , 43 ]. Schweigert et al reported a significantly increased postoperative mortality (OR = 8.24, p = 0.025) for EP compared to YP who present an anastomotic leakage [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies assessed long-term survival among EP compared to YP treated by surgery for esophageal cancer (Table 2). Fourteen studies found a significantly shorter overall survival for EP [25,29,32,34,36,38,40,43 Eleven studies reported disease-free or disease-specific survival (Table 2). Only four authors found a disease-free survival advantage for YP [29,38,43,49], suggesting that no robust suggestions for earlier cancer recurrence in EP can be made.…”
Section: Long-term Survival After Surgerymentioning
confidence: 99%
“…Recently, the number of the elderly esophageal cancer patients has been rapidly growing. Elderly esophageal cancer patients generally have co-morbidities and age-related physiological problems (6)(7)(8). Previous reports have shown that the postoperative surgical complication rates after esophagectomy are 30% to 70%, and the mortality rate is 1%-5% (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Recognizing these limitations, the implications of our report are that this treatment was able to reproduce the results of the phase II trial in various real-world settings without difficulty and that this therapy can be used flexibly even in elderly patients. To date, the aging of population has been progressing and elderly patients with esophageal cancer are more likely to be treated with CRT or RT alone, instead of surgery, for comorbidities and treatment risks [29,30]. Salvage PDT is reported to be a safer and more effective treatment option than other minimally invasive treatments such as re-irradiation or endoluminal brachytherapy in elderly patients [31,32].…”
Section: Discussionmentioning
confidence: 99%